Microfacies characteristics of carbonate cobble from Campanian of Slovenj Gradec (Slovenia): implications for determining the Fleuryana adriatica De Castro, Drobne and Gušić paleoniche and extending the biostratigraphic range in the Tethyan realm (Rudarsko-geološko-naftni zbornik, 2018)
A carbonate cobble was collected in a creek near Slovenj Gradec (Slovenia). It comprises Trochactaeon gastropods as well as foraminifera Fleuryana adriatica and Cuneolina ketini from a subtidal environment with agglutinated and porcelaneous benthic foraminifera. Packstone-grainstone of the structural type contains the abovementioned foraminiferal taxa, which are previously undetermined in this part of the Upper Cretaceous Tethyan realm. Stratigraphic data from this area, together with the determined microfossil assemblage of the carbonate cobble, indicate the upper part of Lower Campanian age, implying an extension of the F. adriatica and C. ketini stratigraphic range. The paleoniche within the Tethyan realm in which F. adriatica thrive is the shallowest part of the subtidal, close to peritidal conditions. It was developed on a relatively harder substrate that resulted from a laterally more pronounced paleorelief which enabled the shifting of hyaline benthic foraminifers towards the shallowest part of the subtidal. Their paleoniche is laterally absent from protected paleoenvironments with soft muddy substrate and a relatively high carbonate sedimentation rate, colonized with elevator rudists, as well as from relatively higher water energy paleoenvironments with completely hard grainstone-rudstone substrate.